1988
DOI: 10.1016/0921-4534(88)90134-7
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on RBa2Cu3Ox materials from oxygen deficiency studies

Abstract: We have measured the electrical resistivity, thermoelectric power, magnetic susceptibility, Hall coefficient and upper critical field near T, in EuBazCu30,, where 6.09 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the optimum-doped YBCO materials, S shows the very weak temperature dependence at high temperatures between 200 K and 300 K and increases linearly with decreasing temperature. A maximum peak just before T c is observed and then S drops to zero [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the optimum-doped YBCO materials, S shows the very weak temperature dependence at high temperatures between 200 K and 300 K and increases linearly with decreasing temperature. A maximum peak just before T c is observed and then S drops to zero [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9 shows a typical plot of the rationalized ac susceptibility of Ba 2 RCu 3 O 7− x [ 31 ] as a function of temperature. The annealing temperatures are indicated from 400 °C to 708 °C.…”
Section: Resultsmentioning
confidence: 99%
“…doi:10.1016/j.jmatprotec.2007.12.078 content, it is found that TEP shows the very weak temperature dependence at high temperatures (T > 200-300 K). TEP increases linearly with decreasing temperature (Forro et al, 1989;Yan et al, 1988;Kwok et al, 1988) which is common TEP behavior in different HT c systems associated with the CuO 2 plane. A maximum peak just before T c is observed which is attributed to the phonon-drag by some researchers.…”
Section: Introductionmentioning
confidence: 93%